Neogene tectono-sedimentary interaction between the Calabrian Accretionary Wedge and the Apulian Foreland in the northern Ionian Sea. (May 2017) - Volpi, V.; Del Ben, A.; Civile, D.; Zgur, F.
Abstract: The structural setting of the northern Ionian Sea is the result of the collision between the Calabrian Accretionary Wedge (CAW) and the adjacent foreland, i.e. the Apulian Carbonate Platform. The CAW represents a sector of the Apennine accretionary system extending in the Ionian Sea, bounded to the west by the Malta Escarpment and to the east by the Apulia Escarpment. This work presents the results of the interpretation of new seismic and bathymetric data acquired on the north-eastern edge of the CAW, in the N-Ionian Sea. The data interpretation has identified four main structural domains from NE to SW: 1. The Apulian carbonate Platform consisting of foreland shelf and transitional Mesozoic-Cenozoic carbonate deposits; 2. A narrow foredeep basin, filled by a very thick Plio-Quaternary succession; 3. A deformed domain, at the front of the CAW, incorporating thrusted foredeep sequences and a carbonate block of the Apulian Platform (Transpressed Apulian Block, TAB); 4. A highly deformed pre-Pliocene accretionary wedge. A mid-Pliocene unconformity interpreted on both the CAW and Apulian Foreland suggests that a regional tectonic event occurred at that time, related to the evolution of Calabrian Arc, moving on the subducting oceanic Ionian slab before the collision. This event would correspond to a main tilting and faulting phase of the Apulian Foreland during the diachronous oblique collision with the CAW. The collision and the presence of a remnant of Ionian foreland at the southern front of the accretionary prism, caused a gradual transition to a transpressional tectonics which produced the uplift of the TAB. The TAB would be the south-east continuation of the Amendolara ridge transpressed structure, which forms the offshore extension of the Pollino range. This transpressed shear zone involving the Apulian Foreland developed above the transition between the Adriatic continental crust and the subducting Ionian oceanic crust. Highlights: New insights in the geodynamic evolution of the north Ionian Sea are provided. Seismo-stratigraphy is based on a recently acquired seismic dataset. The tectonic domains are: Calabrian Arc accretionary wedge; Apulian foreland. The west Apulia margin has played a fundamental role in the chain migration. Re-location of the Calabrian accretionary wedge/Apulian platform domains.